Who's afraid of Trump in the White House? How German firms view the US election - Andreas Baur; Lisandra Flach; Sebastian Link; Andreas Peichl (CESifo GmbH, 2024)
How do German firms view the upcoming US election and a possible second Donald Trump presidency? As part of the ifo Business Survey in September 2024, more than 2,000 German manufacturing firms were asked about the US election. 44 percent of German manufacturing firms anticipate negative impacts on their business situation if Donald Trump wins the election, compared to a potential Kamala Harris presidency.
Keywords: 330